2022
DOI: 10.3389/fgene.2022.849437
|View full text |Cite
|
Sign up to set email alerts
|

Novel Prognostic Signature for Acute Myeloid Leukemia: Bioinformatics Analysis of Combined CNV-Driven and Ferroptosis-Related Genes

Abstract: Background: Acute myeloid leukemia (AML), which has a difficult prognosis, is the most common hematologic malignancy. The role of copy number variations (CNVs) and ferroptosis in the tumor process is becoming increasingly prominent. We aimed to identify specific CNV-driven ferroptosis-related genes (FRGs) and establish a prognostic model for AML.Methods: The combined analysis of CNV differential data and differentially expressed genes (DEGs) data from The Cancer Genome Atlas (TCGA) database was performed to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…All these subgroups could be classified as high or low risk according to NRG score, and there was a significant difference in OS rates between NRG score groups ( p < 0.0001), which indicated that NRG characteristics performed well in the stratified analysis and demonstrated the robustness of the prognostic value of NRG characteristics. Further, we compared NRG score with other signatures in recently published studies 17–19 . These signatures were genes associated with ferroptosis, immunity, and the most significant prognosis respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All these subgroups could be classified as high or low risk according to NRG score, and there was a significant difference in OS rates between NRG score groups ( p < 0.0001), which indicated that NRG characteristics performed well in the stratified analysis and demonstrated the robustness of the prognostic value of NRG characteristics. Further, we compared NRG score with other signatures in recently published studies 17–19 . These signatures were genes associated with ferroptosis, immunity, and the most significant prognosis respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Further, we compared NRG score with other signatures in recently published studies. [17][18][19] These signatures were genes associated with ferroptosis, immunity, and the most significant prognosis respectively. Compared to them, the area under the five-year ROC curve of the NRG score was highest in the training and test set patients (Figure S3G).…”
Section: Applicability and Superiority Of Nrg Scorementioning
confidence: 99%
“…In another study, investigators have identified and verified seven ferroptosis-related lncRNA signatures (AP001266.2, AC133961.1, AF064858.3, AC007383.2, AC008906.1, AC026771.1, and KIF26B-AS1) with independent prognostic value in patients with AML (Table 1) [35]. In summary, we conducted and validated a novel ferroptosisrelated prognostic model for outcome prediction and risk stratification in AML, with great potential to guide individualized treatment strategies in the future [31,[36][37][38].…”
Section: Leukemiamentioning
confidence: 99%
“…Interestingly, many FRG signatures are associated with immune-related pathways and immune cell infiltration predicted by CIBERSORTx gene-expression profiling analyses, which suggests that ferroptosis has relevance in anti-tumor immune responses and potentially in immunotherapy in leukemia. In addition to FRGs’ expression levels, their methylation status [ 180 ] and copy number variations [ 181 ] have also been reported to have prognostic significance. One group studying the correlation of long non-coding RNAs (lncRNAs) and FRGs identified ferroptosis-related lncRNA signatures that predict the prognosis of AML [ 182 ].…”
Section: Ferroptosis In Leukemiamentioning
confidence: 99%